French Ministry of Health's response to Paris attacks of 13 November 2015. Issue 1 (December 2016) - Philippe, Jean-Marc; Brahic, Olivier; Carli, Pierre; Tourtier, Jean-Pierre; Riou, Bruno; Vallet, Benoit
Abstract On Friday November 13th at 9:20 pm, three kamikaze bombs went off around the Stade de France a stadium in Saint-Denis just outside Paris, 4 different shootings took place and bombings in Paris and hundreds of people were held hostage in a theater. This multi-site terrorist attack was the first of this magnitude in France. Drawing the lessons of these attacks and those which occurred in other countries from a health perspective is essential to continuously adapt and improve the French response to possible future attacks. Several issues would need to be further explored:Management of uncertainties: When to trigger the plans: after the 1st attack, the 2nd? When do attacks end and when to release mobilized resources? Management of victims: How to ensure that all victims are secured or taken care of? How to provide assistance when attacks are ongoing? Management of teams: Proper follow-up of persons involved in the response: health professionals, police and firemen, emergency call centers but also civil servants within administration that contributed to the response. Communication: Reactivity of all is a key element to secure appropriate resource is mobilized for the response. All actors have to be able to communicate quickly in a secured way.